Role of Acupuncture and Fire Cupping in Reducing the Thyroxine Dose and Improving the Thyroid Function in Hypothyroidism Patients: A Case Series - Pradeep M. K. Nair; Naga Jyothi (Medical Association of Pharmacopuncture Institute, 2021)
Hypothyroidism is one of the most common endocrine disorders linked to various systemic diseases ranging from obesity to cancers. The present line of management is insufficient as reports suggest that there is persistence of symptoms and poor adherence that makes the management of said disease challenging. Acupuncture and other Traditional Chinese Medicine (TCM) therapies are proven to alleviate endocrine dysfunctions. However, reports on acupuncture and cupping therapy on hypothyroidism are very scarce. Here, we report 5 cases of hypothyroid patients aged between 38-44 yrs who were treated with acupuncture and fire cupping for a period of three months. At the baseline, the patients presented with either a weak, wiry or vacuum pulse which represents spleen Qi deficiency. Further, they presented with elevated levels of Thyroid Stimulating Hormone (TSH), and higher Body Mass Index (BMI). Acupuncture treatment at ST36, LI4, SP6, and BL20 was given bilaterally whilst CV4, LR3, LR4, SP9, ST40, SP10, GV4, KI3, ST12, and SI17 were punctured unilaterally. At the end of the time period of three months, patients progressed to normal levels of TSH, reduction in BMI and had succeeded in tapering their medication doses. Supplementing this, the patients reported marked improvement in other symptoms like fatigue, hair loss, and cold feet post-treatment. The effects were consistent even during the three month follow-up period post-interventions. The results encourage the utilization of acupuncture and fire cupping in the management of hypothyroidism. However, large scale studies are warranted to strengthen this recommendation.